Modern biotechnology in school education from the perspective of foreign research - Horniaková, Michaela (Scientia in educatione, 2024)
The present review study examines foreign educational research that explores knowledge in relation to respondents’ preconceptions and misconceptions about modern biotechnology. Thus, the aim of the study is to provide a comprehensive overview of existing foreign research that focuses primarily on knowledge and, in particular, on preconceptions and misconceptions in this area. The study focuses on the analysis of foreign research from 2000 to 2023. The research was carried out in the Web of Science and Scopus databases using key words/terms. It analyses the objectives of the research, the methods used, the results of the research and its recommendations for the future. The results of the international research show that students’ knowledge of modern biotechnology is minimal and that they lack a conceptual understanding of biotechnology as a whole. In conclusion, the study focuses on the evaluation of students’ pre-conceptual work in the context of the results section of the review study. It highlights the theory that deals directly with students’ preconceptions and then proposes a possible approach that can be applied to work with preconceptions and to address students’ misconceptions specifically in science education. This review study can serve as a basis for further research or the development of pedagogical strategies aimed at improving the teaching of biotechnology and the understanding of preconceptions and misconceptions, not only among students.